Effect of Essential Oil and Extracts From Oregano (Origanum onites L.) Leaves on the Oxidative Stability of Refined Sunflower Oil - Sami Kunduraci, Bekir; Bayrak, Ali; Kiralan, Mustafa (Asian Journal of Chemistry, 2010)
The antioxidant activity of oregano essential oil, ethanol extract, hexane extract and deodorized ethanol extract, deodorized hexaneextract from oregano (Origanum onites L.) leaves were evaluated in refined sunflower oil using by Schaal oven and Rancimat method. The main component in oregano essential oil, carvacrol was also used evaluated. In Schaal oven test, peroxide value and specific absorption at 232 nm were used in determination of oxidation at 60 ºC. Rancimat apparatus monitored the oxidation of oils at 110 °C to get information about effects of added extracts and oregano essential oil at elevated temperature. Among extracts, hexane extract at 0.1 % concentration exhibited stronger antioxidant activity than deodorized ethanol extract (0.1 %), deodorized hexane extract (0.1 %) and ethanol extract (0.1 %) showed in Schaal oven test at 60 ºC. The effect of the extracts was less significant in Ransimat test. Only hexane and ethanol extracts showed activity, however the other extracts didn't show any activty in Ransimat test. Oregano essential oil and carvacrol didn't influence oxidation stability of refined sunflower oil in tests used.